A bitter future for coffee production? Physiological traits associated with yield reveal high vulnerability to hydraulic failure in Coffea canephora. (21st December 2022) - Max, Aldo Custódio; Loram‐Lourenço, Lucas; Silva, Fabiano Guimarães; de Souza, Luan Henrique Martiniano; Dias, Jairo Rafael Machado; Espíndula, Marcelo Curitiba; Farnese, Fernanda S.; Hammond, William; Torres‐Ruiz, José M.; Cochard, Hervé; Menezes‐Silva, Paulo Eduardo
Abstract: The increase in frequency and intensity of drought events have hampered coffee production in the already threatened Amazon region, yet little is known about key aspects underlying the variability in yield potential across genotypes, nor to what extent higher productivity is linked to reduced drought tolerance. Here we explored how variations in morphoanatomical and physiological leaf traits can explain differences in yield and vulnerability to embolism in 11 Coffea canephora genotypes cultivated in the Western Amazon. The remarkable variation in coffee yield across genotypes was tightly related to differences in their carbon assimilation and water transport capacities, revealing a diffusive limitation to photosynthesis linked by hydraulic constraints. Although a clear trade‐off between water transport efficiency and safety was not detected, all the studied genotypes operated in a narrow and/or negative hydraulic safety margin, suggesting a high vulnerability to leaf hydraulic failure (HF), especially on the most productive genotypes. Modelling exercises revealed that variations in HF across genotypes were mainly associated with differences in leaf water vapour leakage when stomata are closed, reflecting contrasting growth strategies. Overall, our results provide a new perspective on the challenges of sustaining coffee production in the Amazon region under a drier and warmer climate. Summary statement: By combining morphoanatomical analysis with modelling exercises, we revealed that traits associated with high yield lead to increased vulnerability to leaf drought‐induced mortality in cultivars of Coffea canephora, evidencing a worrying scenario for coffee production in a warmer and drier world.